Plan de negocios para la exportación de uchuva a la ciudad de México, México (2018)
This business plan for the export of Uchuva by the company Frutcous, is made with the objective of determining the economic and financial viabilitu of the project, implementing strategies that generate a successful export and achieve increased production for the development of the sector, this allowing an expansion of exports for a larger international market. The whole pertinent study was carried out, beginning with the market study directed specifically to Mexico City due to its large surface and population size, where it is determined that it is a destination for the export of cape gooseberry, due to its great acceptance of the product and the derived products that are taken out of the fruit.